Предельные полномочия: роман / Сергей Зверев - Зверев Сергей Иванович (Спецназ ВДВ, 2011)
Экземпляры: АБ (20140326) / Инвентарный номер: 1 / Цена: 45.00 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6